Ultrasound of Thyroid Nodules Ultrasound Characteristics and Risk of Carcinoma - Schmidt, Daniela (Laryngo-Rhino-Otologie, 2019)
Thyroid ultrasound is used as a first-line diagnostic procedure to evaluate thyroid nodules. Several ultrasound characteristics have been associated with an increased risk of malignancy. Based on these criteria, classification systems are being developed to categorize thyroid nodules and stratify their malignant risk to decide about further evaluation. Up to now only morphological features are taken into account. The results of Doppler ultrasonography have not yet been included in these thyroid imaging and reporting systems (TI-RADS) although predominantly internal flow is associated with malignancy of thyroid follicular neoplasia. Currently, the new systems will be evaluated and may be optimized for clinical practice. Furthermore there are first attempts to standardize the reporting of ultrasound features of thyroid nodules to enhance patient care by optimizing the diagnostic capabilities of an ultrasound examination.
CRIS-Team WoS Importer:2019-03-06